A case report of Cogan's syndrome with recurrent coronary stenosis - Na, Gao; Nan, Zhang; Jingjing, Meng; Lili, Pan (Frontiers in Cardiovascular Medicine, 2024)
Cogan's syndrome (CS) is recognized as a form of variable vasculitis. This report presents the case of a middle-aged woman experiencing recurrent coronary artery stenosis, accompanied by a history of non-syphilis keratitis, vestibular auditory symptoms, and venous thrombosis. Positron emission tomography/computed tomography (PET/CT) revealed elevated uptake of (18)Ffluorodeoxyglucose (18F-FDG) in the subclavian artery, common carotid artery, aortic arch, and thoracic aorta. A diagnosis of Cogan's syndrome was made. The aim of this study is to enhance clinicians' awareness of the vascular manifestations in CS and to emphasize the importance of thorough history taking. CS should be included in the differential diagnosis when patients present with recurrent coronary artery stenosis.